Legal Protection for Good Faith Buyers in Land Sale and Purchase Transactions (Study of Decision Number 3915 K/Pdt/2022) - Irene, Irene; Tjempaka, Tjempaka (Journal of Law, Politic and Humanities, 2024)
Land is an essential need for humans. Because it is used to fulfill basic human needs such as shelter and food production. Land is used to meet human needs. Soil is an important part of human life. What needs to be understood is that land is a place to live, as a means of residence and humans obtain land by managing and utilizing land as much as possible. In the utilization and acquisition of land, of course there is government involvement and authority. In writing this thesis, the author raised a dispute case originating from the Supreme Court Court Decision Case Number 3915 K/Pdt/2022. Initially, the Plaintiff (PT Grow Selamat Makmur) and the Defendant (PT Surya Cipta Khatulistiwa) were involved in a sale and purchase agreement for 24 plots of land in Bogor Regency through Deed No.05 dated 16 July 2018. These lands had title certificates, including Title Certificates. Building Use and Use Rights Certificates, with details of 15 Building Use Rights Certificates and 9 Use Rights Certificates. In this agreement, it was agreed that the land price would be Rp. 550,000/m2, as well as payment procedures which reach a total of Rp. 119,560,000,000, although the land area has not been re-measured by the local Land Agency, the Buyer (Plaintiff) has paid the price according to the agreement. Based on the problems studied, the type of research is normative legal research, where law is conceptualized as what is written in statutory regulations (law in books) or law is conceptualized as rules or norms which are benchmarks for human behavior that is considered appropriate. Normative legal research refers to legal norms contained in regulations or laws related to Supreme Court Decision No. 3915 K/Pdt/2022.